Evaluation of biomechanical variables in the task of laying the casing: a case study - Moreira, Isabella Cristina Pereira; Arão , Isabelle Rocha; Soares, Helen Pereira dos Santos; Lima, Karla Kellem de; Junior, Ronaldo Rosa dos Santos; Ucker, Fernando Ernesto; Santos, Luana Machado dos (Seven Editora, 2023)
The present work aims to analyze the numerous biomechanical variables observed during the execution of the laying task by a mason. For this, a research method based on the case study was developed, in which photographic records were made of the different stages that make up the activity. Such steps consist of loading of materials, preparation of the mortar, application of the mass on the wall, and laying of the ceramic piece. Biomechanical variables such as load lifting, repetitiveness, muscle contraction, mechanical compression, and inadequate posture were found. Through the analysis and discussion of the literature, measures were presented to be implemented in the worker’s routine to minimize biomechanical risks, thus generating a safer and healthier work environment. Therefore, when the worker is in a favorable work environment, he is more productive. Investment in the ergonomic area within civil construction brings benefits, through productivity and minimization of expenses with occupational diseases and accidents at work. DOI:https://doi.org/10.56238/methofocusinterv1-049